Analysis of Thyroid Disorders in the Occurrence of Paroxysmal Atrial Fibrillation - Dwiyanto, Yusup; Amelia Andini (Global Indonesia Health Care (GOICARE), 2024)
Thyroid disorders can directly affect the cardiovascular system, especially atrial fibrillation arrhythmia. Atrial fibrillation can be triggered by hormonal changes in the human body system. This can be dangerous and can increase the risk of stroke in sufferers. For this reason, researchers conducted this study to be able to analyze the risk of atrial fibrillation due to thyroid disorders. This study used a retrospective analytical design, with a chi square test to determine the risk of increased atrial fibrillation due to thyroid disorders. This study was conducted at Budhi Asih Hospital with Holter monitoring patient samples. The results of this study showed that in patients with thyroid disorders, the results of Holter monitoring showed paroxysmal atrial fibrillation as much as 9.9%, with a p-value: 0.000; OR: 39.346. The conclusion is that there are significant results between thyroid disorders and the incidence of paroxysmal atrial fibrillation